2018
DOI: 10.1126/science.aar6464
|View full text |Cite
|
Sign up to set email alerts
|

CORNICHON sorting and regulation of GLR channels underlie pollen tube Ca 2+ homeostasis

Abstract: Compared to animals, evolution of plant calcium (Ca) physiology has led to a loss of proteins for influx and small ligand-operated control of cytosolic Ca, leaving many Ca mechanisms unaccounted for. Here, we show a mechanism for sorting and activation of glutamate receptor-like channels (GLRs) by CORNICHON HOMOLOG (CNIH) proteins. Single mutants of pollen-expressed GLRs (GLRs) showed growth and Ca flux phenotypes expected for plasma membrane Ca channels. However, higher-order mutants of GLR3.3 revealed phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
134
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 47 publications
1
134
0
1
Order By: Relevance
“…The presence of glutamatergic synapses in non-neuronal, epithelial cells of the Drosophila wing disc and ASP is unexpected and without precedent, but is consistent with a comparative analysis of the GluR gene family that concluded that GluR signaling is present even in animals that lack a nervous system, such as Trichoplax (57). Plants also regulate Ca 2+ influx with GluR-like channels that are required for growth and cell-cell communication (58, 59).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of glutamatergic synapses in non-neuronal, epithelial cells of the Drosophila wing disc and ASP is unexpected and without precedent, but is consistent with a comparative analysis of the GluR gene family that concluded that GluR signaling is present even in animals that lack a nervous system, such as Trichoplax (57). Plants also regulate Ca 2+ influx with GluR-like channels that are required for growth and cell-cell communication (58, 59).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in plants, in addition to above-mentioned functions, Glu is found to emerge as a novel signaling role in many physiological processes. These processes include seed germination (Kong et al, 2015), root architecture (Forde, 2014;López-Bucio et al, 2019), pollen germination and pollen tube growth (Michard et al, 2011;Wudick et al, 2018), wound response and pathogen resistance (Manzoor et al, 2013;Mousavi et al, 2013;Nguyen et al, 2018;Toyota et al, 2018;Jin et al, 2019), and response and adaptation to abiotic stress (Cheng et al, 2018;Zheng et al, 2018;Li H. et al, 2019;Philippe et al, 2019). In addition, Glu can act as a long-distance signaling transducer among cells, tissues, organs, and even the whole plants by the crosstalk with Ca 2+ , ROS, and electrical signaling (Mousavi et al, 2013;Nguyen et al, 2018;Toyota et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Glu can act as a long-distance signaling transducer among cells, tissues, organs, and even the whole plants by the crosstalk with Ca 2+ , ROS, and electrical signaling (Mousavi et al, 2013;Nguyen et al, 2018;Toyota et al, 2018). Numerous studies have showed that Glu usually exerts signaling role by its receptors, that is, glutamate receptors (GLRs), similar to iGluRs in animals (Lam et al, 1998;Wudick et al, 2018;López-Bucio et al, 2019). In plants, GLRs are at least classified into three clades: clade I (GLRs 1.1-1.4), clade II (GLRs 2.1-2.9), and clade III (GLRs 3.1-3.7) (Lam et al, 1998;Weiland et al, 2016;Wudick et al, 2018;López-Bucio et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant cells, such as the pollen grains and pollen tubes, play a key role in plant sexual reproduction, and serve as model systems for cellular morphogenesis. Pollen, also known as the male gametophyte of flowering plants, carries and transports the two sperm cells within its cytoplasm.…”
Section: Introductionmentioning
confidence: 99%